The Effect of Implementation Project-Based Learning (PJBL) on Students’ English Learning Outcomes - Afrianti, Indah; Rusdin; Nur Wahyuni; Arifin, Arifin; Putra, Muhamad Yanbagi Abidin (International Journal of English and Applied Linguistics (IJEAL), 2025)
The objective of this study is to ascertain the impact of implementing PjBL on the English learning outcomes of students at MAN 1 Dompu in the 2024 academic year. The present research employed a pre-experimental method with a one-group pre-test–post-test design using a quantitative approach. The population under study comprised all 216 eleventh-grade students. The sample population for this study comprised 25 students from class XI Science 2, which was designated as the experimental class. Sixteen students participated in the pre-test and seventeen in the post-test. The purposive sampling technique was utilized in this study. The data were collected through the administration of pre-tests and post-tests and subsequently analysed using a normality test. The pre-test results demonstrated an average score of 57, while the post-test average increased to 80, indicating an improvement of 23 points. Subsequent analysis of the post-test data was conducted using a t-test, which yielded a t-count of 1.728. The obtained value of 0.104 was then compared with the threshold of 0.05. In consideration of the findings, a statistically significant discrepancy was identified in the student learning outcomes before and after the implementation of PjBL. In reference to the proposed hypotheses Ha: there is an effect of applying the PjBL model on the learning outcomes of MAN 1 Dompu students, and H?: there is no such effect the findings support the acceptance of Ha. Consequently, it can be concluded that the implementation of PjBL had a positive effect on the English learning outcomes of MAN 1 Dompu students in the 2024 academic year.